Judicial Control over Prolonged Criminal Investigations: Pretrial Remedies in the Light of Progressive Law - Andi Muhammad Alqadri Syarif; Ahmad Syahird; Besse Sari Angraeni (LEGAL BRIEF, 2026)
The absence of a clear time limit for criminal investigations under the Indonesian Criminal Procedure Code (KUHAP) has frequently resulted in protracted investigations, effectively keeping individuals in a state of perpetual suspecthood. Textually, Article 77 of KUHAP limits the scope of pretrial review (praperadilan) to a closed list, without explicitly including investigation delays as a reviewable matter. This limitation generates legal uncertainty for suspects and impedes the protection of fundamental human rights guaranteed in criminal proceedings. This study examines the urgency of expanding the scope of pretrial review to encompass unduly prolonged investigations. Using a qualitative method with a normative-juridical approach, it analyzes primary, secondary, and tertiary legal materials to identify legal gaps and propose normative solutions. The findings indicate that investigations prolonged without reasonable justification violate human rights and undermine the principles of prompt, simple, and low-cost justice. From a progressive law perspective, pretrial applications challenging undue delay should be admissible to prevent abuse of authority by investigators. Consequently, unreasonably prolonged investigations lacking active and genuine investigative measures should be construed as a form of material termination of investigation. The study recommends that pretrial judges apply progressive legal reasoning (rechtsvinding) to accept such applications, thereby ensuring legal certainty and restoring the rights of suspects affected by defective judicial administration